Surgical management of adult Hirschsprung’s disease by subtotal colectomy: a possible alternative - Kildušis, Edvinas; Poškus, Tomas; Strupas, Kęstutis (Lietuvos chirurgija, 2016)
Adult Hirschsprung’s disease (AHD) is a rare and often undiagnosed condition. At present, only a limited number of cases have been reported. We managed a 19-year-old woman with rich history of chronic constipation and abdominal discomfort. Abdominal radiography and barium enema examination demonstrated massively dilated colon (up to 15 cm in diameter). Full-thickness rectal biopsy showed absence of ganglionic cells. AHD was diagnosed and subtotal colectomy with ileorectal anastomosis was performed. At five-year follow up, the patient had significantly improved defecation and quality of life and was extremely satisfied with the operation. AHD should be considered in patients with long-standing and refractory constipation with megacolon. We advocate a subtotal colectomy with ileorectal anastomosis as one of the possible surgical alternatives in such young patients.
Keywords: adult Hirschsprung’s disease; constipation; megacolon; aganglionosis